2017
DOI: 10.1002/adfm.201701870
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of P2‐Na0.66(Mn0.54Co0.13Ni0.13)O2 Cathode for Sodium‐Ion Batteries by Ultrathin Metal Oxide Coatings via Atomic Layer Deposition

Abstract: Sodium-ion batteries are widely considered as promising energy storage systems for large-scale applications, but their relatively low energy density hinders further practical applications. Developing high-voltage cathode materials is an effective approach to increase the overall energy density of sodium-ion batteries. When cut-off voltage is elevated over 4.3 V, however, the cathode becomes extremely unstable due to structural transformations as well as metal dissolution into the electrolytes. In this work, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 56 publications
1
108
0
Order By: Relevance
“…It should be emphasized that the type of ALD‐engineered layer for SIBs determines the other electrochemical parameters . Kaliyappan et al first utilized ALD to construct a nanoscale metal oxide coating on the surface to promote the capacity retention of a P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (MCN) cathode at high cut‐off voltages (2–4.5 V), as shown in Figure . The researchers investigated the modification effects of Al 2 O 3 , ZrO 2 , and TiO 2 coating layers by comparing ALD‐Al 2 O 3 P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (ALD‐MCN), ALD‐ZrO 2 P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (Zr‐MCN), and ALD‐TiO 2 P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (Ti‐MCN).…”
Section: The Electrode Engineering Of Traditional Sib Materials Desigmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that the type of ALD‐engineered layer for SIBs determines the other electrochemical parameters . Kaliyappan et al first utilized ALD to construct a nanoscale metal oxide coating on the surface to promote the capacity retention of a P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (MCN) cathode at high cut‐off voltages (2–4.5 V), as shown in Figure . The researchers investigated the modification effects of Al 2 O 3 , ZrO 2 , and TiO 2 coating layers by comparing ALD‐Al 2 O 3 P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (ALD‐MCN), ALD‐ZrO 2 P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (Zr‐MCN), and ALD‐TiO 2 P2‐Na 0.66 (Mn 0.54 Co 0.13 Ni 0.13 )O 2 (Ti‐MCN).…”
Section: The Electrode Engineering Of Traditional Sib Materials Desigmentioning
confidence: 99%
“…d) Charge/discharge profiles and e) cycle life of pristine and MCN electrode with metal oxide coatings at 0.16 A g −1 (1 C rate) current density within 2–4.5 V. f) Rate capability of the electrodes at different current densities and g) Nyquist plots of MCN and MCN coated with different metal oxides recorded at open circuit voltage. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: The Electrode Engineering Of Traditional Sib Materials Desigmentioning
confidence: 99%
“…Due to the large abundance and low cost of sodium resources and similar chemical/electrochemical properties to established lithium‐ion batteries (LIBs), room temperature sodium‐ion batteries (SIBs) emerge as a potential technology for grid‐scale energy storage . A large number of materials, such as transition metal oxides, phosphates, ferrocyanides, metal alloys, and hard carbon, have been investigated and have shown acceptable electrochemical performance, and some reviews have summarized recent developments in electrodes for SIBs . However, due to the higher molar weight of the Na element and more positive standard electrochemical potential of Na/Na + (compared to Li/Li + ), SIBs exhibit lower energy densities than LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, even at a high rate of 5 C, the 0.1 K‐NaMCN electrode delivers a high capacity of 105.5 mAh g −1 in contrast to 51.9 mAh g −1 for the NaMCN. Compared with other P2‐type layered oxides reported previously, 0.1 K‐NaMCN also exhibits superior high‐rate performance (Table S3) . Charge‐discharge profiles at different rates of the NaMCN and 0.1 K‐NaMCN electrodes are showed in Figure e and 5 f, obviously, the NaMCN electrode exhibits a much higher polarization and the voltage plateaus vanish gradually as the rate increases, reflecting a diffusion‐limited process at high rates.…”
Section: Resultsmentioning
confidence: 65%
“…reported that sodium phosphate (NaPO 3 ) nanolayers help scavenge the HF and H 2 O in the electrolyte and inhibit the accumulation of corrosion products on the surface, thereby improving the rate performance . Coating materials with fast ion‐conductivity have also been proposed to play a role in accelerating the Na + transport near the electrode surface . Although these modification methods take effect in improving the Na + diffusion efficiency at the cathode‐electrolyte interface, the Na + conduction capability in the bulk has not been improved.…”
Section: Introductionmentioning
confidence: 99%